2014
DOI: 10.12669/pjms.306.5648
|View full text |Cite
|
Sign up to set email alerts
|

Injury incidence and balance in rugby players

Abstract: Objective : This study determined and correlated injury incidence and balance in rugby players. Methods: A prospective survey with balance testing was conducted on first year rugby academy players (N= 114). Injury incidence, static and dynamic balance were tested pre and post-season using a Biosway portable balance system. The data was analysed using paired and independent samples t-tests at p<0.05, Odds ratios, and Spearman’s correlation coefficients. Results: 75.50% participated, 71.40% were 18 years old, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…The second task was the unilateral stance assessment (ULSA), which has been utilised in rugby academy players and has shown good to excellent test-retest reliability [ 32 ]. Participants were asked to stand on their right foot with their eyes open (REO) and then closed (REC) and then on their left foot with their eyes open (LEO) and then eyes closed (LEC) for 30 s in each trial.…”
Section: Methodsmentioning
confidence: 99%
“…The second task was the unilateral stance assessment (ULSA), which has been utilised in rugby academy players and has shown good to excellent test-retest reliability [ 32 ]. Participants were asked to stand on their right foot with their eyes open (REO) and then closed (REC) and then on their left foot with their eyes open (LEO) and then eyes closed (LEC) for 30 s in each trial.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, in this study, the aim was to evaluate differences in postural control and balance for two very different sports, taekwondo (TKD) and tennis, where TKD principally involves kicking, while tennis eye-hand coordinated movements performed during sprints, with quick changes in speed, and fast cutting motions 9 , 10 , 12 ) . Knowing that posture control strongly influences sports performance and injuries 13 , 14 , 15 , 16 ) and that TKD and tennis are popular among children and adolescents, the study specifically sought to compare and contrast balance strategies in young athletes who trained for either TKD or tennis.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Several studies have indicated that poor balance is associated with an increased risk of LE injury. 11 , 15 , 16 , 22 Therefore, the use of quantitative athlete movement-screening tests measuring LE balance may be useful for sports medicine professionals to identify athletes at risk for injury. Additionally, predetermined benchmarks on these tests can serve as objective measures of the amount of improvement an athlete has made during rehabilitation and when an athlete can safely return to play after injury.…”
mentioning
confidence: 99%